Daguerreotypes : fugitive subjects, contemporary objects - Saltzman, Lisa (University of Chicago Press, 2015)
"In the digital age, photography confronts its future under the competing signs of ubiquity and obsolescence. While technology has allowed amateurs and experts alike to create high-quality photographs in the blink of an eye, new electronic formats have severed the original photochemical link between image and subject. At the same time, recent cinematic photography has stretched the concept of photography and raised questions about its truth value as a documentary medium. Despite this situation, photography remains a stubbornly substantive form of evidence: referenced by artists, filmmakers, and writers as a powerful emblem of truth, photography has found its home in other media at precisely the moment of its own material demise. By examining this idea of photography as articulated in literature, film, and the graphic novel, Daguerreotypes demonstrates how photography secures identity for figures with an otherwise unstable sense of self. Lisa Saltzman argues that in many modern works, the photograph asserts itself as a guarantor of identity, whether genuine or fabricated. From Roland Barthes's Camera Lucida to Ridley Scott's Blade Runner, W.G. Sebald's Austerlitz to Alison Bechdel's Fun Home--we find traces of photography's "fugitive subjects" throughout contemporary culture. Ultimately, Daguerreotypes reveals how the photograph, at once personal memento and material witness, has inspired a range of modern artistic and critical practices."--Publisher's description